Using Failure Mode, Effect and Criticality Analysis to improve safety in the cancer treatment prescription and administration process - Alessandra Buja; Giuseppe De Luca; Ketti Ottolitri; Elena Marchi; Francesco Paolo De Siena; Giovanni Leone; Pietro Maculan; Umberto Bolzonella; Riccardo Caberlotto; Giovanni Cappella; Giulia Grotto; Gaia Lattavo; et al. (Taylor & Francis Group, 2023)
Key points FMECA is a proactive risk assessment tool that has proved useful in identifying potential failures in the process of prescribing and administering cancer treatments, which is a high-risk process. The analysis evidenced 22 failures modes, distributed over the various phases of the process. In order to reduce the likelihood of the cause, or to improve the chances of a failure mode being detected, this work identified a number of recommendations to be adopted in the administration of cancer treatment in an outpatient setting.